Life after extinction: palaeoenvironments of the earliest Triassic lower Katberg formation, including the origin of Lystrosaurus Bonebeds from the Karoo Basin, South Africa - Viglietti, Pia A (Department of Geological Sciences, 2015)
Includes abstract.